Online peer support for people with Young Onset Dementia: development of a best practice guidance - Gerritzen, Esther Vera (2023)
Introduction: Peer support can be very valuable for people with Young Onset Dementia (YOD) (diagnosis before the age of 65). People with YOD face unique challenges compared to older adults and often experience stigma. YOD can have a negative impact on someone’s sense of self, identity, and social roles in the community. Peer support provides social opportunities where people experience mutual understanding and empathy because they are all experiencing similar challenges. People also exchange practical information on dementia and signpost support services. In the United Kingdom, availability of age-appropriate, in-person peer support services is inconsistent, and many people may miss out on the potential benefits. Online peer support could be a solution, as it overcomes geographical barriers and offers a variety of platforms and modes of communication. The aim of this thesis was to develop a Best Practice Guidance on online peer support for people with YOD, and specific guidelines for peer support facilitators.